Development of Sorbent Materials based on Polymer Waste and their Compounds with Nanomaterials for Oil Spill Remediation - Torres, Cynthia E.I.; Quezada, Thelma S.; López, Israel; de la Fuente, Idalia G.; Rodríguez, Francisco E.L.; Kharissova, Oxana V.; Kharisov, Boris I. (Recent Patents on Nanotechnology, 2020)
Aims: The purpose of this work was to obtain a hydrophobic sorbent material with potential applications in oil spill remediation. Background: The accidents due to oil spills cause long-term ecological damage, especially in the aquatic environment. The cleaning of oil spills can be carried out by many methods and techniques, being absorbents the most attractive due to the possibility of recovery and complete elimination of the hydrocarbons in situ from the water surface. In recent years, interest in polymeric materials for oil spill remediation has increased due to its low cost, high stability, and recyclability. Objective: The objective of this work was the development of sorbent materials based on polymer wastes, such as Polyethylene Terephthalate (PET), obtained from recycled bottles, and recycled Polyurethane (PU), for its application in the recovery of oil spills. Methods: Sorbent materials were prepared from polymer wastes, using salt molds for the formation of porous materials with a composition of PU of 5, 10 and 15%, which were subsequently hydrophobized using carbon nanotubes or silica nanoparticles by dip-coating technique. Results and Discussion: The obtained hydrophobic sorbent materials were characterized by Scanning Electron Microscopy (SEM) and Infrared Spectroscopy (FTIR). The resulting absorbent has shown capacity to separate oil from water; the best result was obtained by the sponge of PET-PU (10% PU) hydrophobized with a suspension with low multi-wall carbon nanotubes (MWCNTs) concentration, obtaining an absorption capacity of 2.01 g/g. Conclusion: Besides the standard sorption capacity, these cheap sorbent materials had interesting properties like low density, high hydrophobicity and buoyancy, which could be applied in other applications related to solving oil spills.
Keywords: sorbents